Initial Experience with Fractionation Mapping in the Identification of Vagal Ganglionated Plexus During Cardioneuroablation - Fabricio Vassallo; Edevaldo da Silva; Lucas Luis Meigre; Christiano Cunha; Eduardo Serpa; Aloyr Simões Jr; Hermes Carloni; Carlos Volponi (Journal of Cardiac Arrhythmias, 2021)
This is a series case report of five symptomatic patients presented with diagnosis of sinus bradycardia, first and second degrees atrioventricular (AV) blocks, that were referred to pacemaker implantation. During the screening, a functional cause for the bradycardia and AV blocks were documented by treadmill stress test, 24-hour Holter monitoring and atropine test. After the confirmation of the diagnosis, patients were submitted to cardioneuroablation on an anatomical basis supported by a tridimensional electroanatomical fractionation mapping software. The technique and the acute and short-term results of the cardioneuroablation are described.